Integrated nitrogen management in increasing yield and economic profitability of broccoli (Brassica oleracea var. italica L.) - Hussain, Md. Jamal; Sirajul Karim, A.J.M.; Solaiman, A.R.M.; Islam, Md. Monirul; Islam, Md. Shafiqul; Laila Naher, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The experiment was conducted at Bangabandhu Sheikh Mujibur Rahman Agricultural University during the period of November 2014 to April 2015 with a view to assess the combined effect of inorganic and organic sources of nitrogen on yield of broccoli and to develop a combined dose under integrated plant nutrition system (IPNS) for broccoli production. Four levels of Nitrogen (N) as 140, 160 and 180 kg N ha-1 as urea super granules (USG) and 180 kg N ha-1 as prilled urea (PU) as well as three different organic nitrogen sources (IPNS based) were considered to comprise 24 treatments combinations. The experiment was laid out in a randomized complete block design with three replications. USG along with organic manures showed better yield performance regarding yield attributes and yield compared to PU. The highest head yield (14.7 t ha-1) was found in USG-N160 kg/ha+ Oil Cake (OC)2t/ha followed by USG-N180kg/ha+ OC2t/ha (14.5 t ha-1). The maximum lateral head yield (6.612 t ha-1), marginal rate of return (132), and benefit cost ratio (4.00) were recorded in USG-N160kg/ha+ Poultry manure (PM)3t/ha. The treatment PU-N180+PM3 also showed better performance regarding yield (13.7 t ha-1), harvest index (27.1%) and benefit cost ratio (BCR) (3.84). Therefore, USG @160 kg N ha-1 + 3 t ha-1 poultry manure as adjusted N126P22K62S14Zn2B1Mo0.8 kg/ ha+3 t/ha PM or PU @180 kg N/ ha + 3 t/ ha poultry manure as adjusted N146P22K62S14Zn2B1Mo0.8 ha+3 t/ ha PM can be recommended for broccoli production in Grey Terrace Soil.